Antiviral activity of red fluorescent proteins in silkworm, Bombyx mori L. - Islam, Tajamul; Qadir, Jasmeena (Journal of Scientific Agriculture, 2024)
Silkworm is an important economic insect in the textile industry for the production of silk. During its larval period, it suffers from various types of diseases viz., fungal, viral, bacterial and protozoan which hamper its growth and development and negatively impact the raw silk production. To fight these pathogens, different types of proteins have been found in the silkworm larva. Among these proteins, red fluorescent proteins (RFPs) possess antiviral activity, found in the digestive juice of the midgut of silkworm larvae. These RFPs are found to be more effective against Bombyx mori L. nucleopolyhedrosis virus (BmNPV), which is the causal agent of the most dreadful disease known as Grasserie. The RFP is synthesised in the presence of light after silkworms are fed on fresh mulberry leaves having absorbance peaks (280 and 605 nm) wave length.